Alternative dispute resolution mechanisms as a human right in due process (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of this work is to carry out a study in relation to how due process is configured in alternative dispute resolution mechanisms, for this, it requires the preparation of mediators as well as the use of techniques and tools that help to configure a due process in the resolution of conflicts of the person. Therefore, good preparation and training of the mediator is needed, so that he can develop a good process of the alternative mechanisms, regardless of whether it is involved; mediation or conciliation, thus creating a correct due process in the solution of a conflict that comes before this type of alternative justice
Keywords: mediation; conciliation; due process; mediator; techniques